Google Classroom: An Effective Virtual Platform to Teach Writing in an EFL Composition Course - Brand Fonseca, Kevin Armando (2019)
In the face of globalization, information communication technologies (ICTs) play a paramount role in the teaching and learning of foreign languages. This action-research was conducted with a group of sophomore students enrolled in the course Composition at Universidad Nacional, Coto Campus. The study required the administration of two surveys prior to and after the implementation of Google Classroom (GC) as an educational platform to assist students during their learning process of the course. The research was aimed at revealing the students’ use ICTs to practice their writing skill outside the classroom and analyzing the impact of GC in the development of the students writing skill out of the school environment. The findings exposed that the use of this platform brings about benefits that allow students and teachers to ease the teaching and learning of writing. Students also expressed that they practice their writing mainly for both academic and non-academic purposes in an engaging attractive space; lastly, students and researchers pointed out that the experience using GC was more satisfactory than other platforms.